2018
DOI: 10.1016/j.mayocpiqo.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Health Care Utilization and Costs of Patients Undergoing Lower Extremity Joint Replacement

Abstract: BackgroundThe Comprehensive Care for Joint Replacement program implemented by the Centers for Medicare and Medicaid Services did not incorporate risk adjustment for lower extremity joint replacement (LEJR). Lack of adjustment places hospitals at financial risk and creates incentives for adverse patient selection.ObjectiveTo identify patient-level risk factors associated with health care utilization and costs of patients undergoing LEJR.MethodsA comprehensive search of research databases from January 1, 1990, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…Our findings are consistent with previously published studies looking at LOS and complication rates in complex TKA patients. 2,4,[10][11][12][13][14] In a study of 516,745 patients from the Nationwide Inpatient Sample, Pugley et al 2 found that greater comorbidities were associated with prolonged LOS, with each additional comorbidity yielding a subsequent increase in LOS. Knoedler et al 10 evaluated 79 studies in their systematic review to find a similar association between an increased number of medical comorbidities and LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with previously published studies looking at LOS and complication rates in complex TKA patients. 2,4,[10][11][12][13][14] In a study of 516,745 patients from the Nationwide Inpatient Sample, Pugley et al 2 found that greater comorbidities were associated with prolonged LOS, with each additional comorbidity yielding a subsequent increase in LOS. Knoedler et al 10 evaluated 79 studies in their systematic review to find a similar association between an increased number of medical comorbidities and LOS.…”
Section: Discussionmentioning
confidence: 99%
“…10 Findings from this current study is consistent with previously published literature on costs in TKA. [11][12][13][14][15][16][17][18] Cram et al 17 studied 167,186 patients from Medicare administrative databases who underwent primary TKAs in 2009 and found that mean Medicare payments for EOC increased from $19,633 for patients with 2 or fewer comorbidities to $27,578 for patients with 5 or more comorbidities (p < 0.0001). Li et al 12 also investigated Medicare payments for patients who underwent TKA in 2009.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of healthcare utilization and costs in lower extremity joint replacement also found that patients with more comorbidities tended to incur greater costs. Knoedler et al 13 included 79 studies in their analysis and found that medical comorbidities, disease severity, and obesity were associated with increased costs. Furthermore, an increased number of medical comorbidities were also associated with a moderate increase in LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Age, because older TKA and THA patients tend to have a longer rehabilitation period [ 42 , 43 ], and 3. Socioeconomic status (SES), because if the costs of care usage is reimbursed through an insurance plan (as is the case for most post-discharge TKA or THA PT care in the Netherlands), then patients with a lower SES tend to utilize more care [ 44 , 45 ]. This SES information was retrieved by merging the study sample using the four-digit postal codes of patients with the national database of Statistics Netherlands (CBS) and categorized in five groups, ranging from low to high SES.…”
Section: Methodsmentioning
confidence: 99%